2020
DOI: 10.14202/vetworld.2020.360-363
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance pattern of extended-spectrum β-lactamase-producing Escherichia coli isolated from fecal samples of piglets and pig farm workers of selected organized farms of India

Abstract: Background and Aim: Extended-spectrum β-lactamase (ESBL)-producing Escherichia coli are gradually increasing worldwide and carry a serious public threat. This study aimed to determine the antimicrobial resistance pattern of ESBL-producing E. coli isolated from fecal samples of piglets and pig farm workers. Materials and Methods: Fecal samples from <3-month-old piglets (n=156) and farm workers (n=21) were processed for the isolation of ESBL-producing E. coli in MacConkey agar added with 1 μg/mL of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…ESBL-producing E. coli strains presented co-resistances to fluoroquinolones ( n = 49), aminoglycosides ( n = 31), TETs ( n = 26) and SXT ( n = 46), confirming previously reported antimicrobial resistance patterns of ESBL-producing E. coli [ 39 , 40 , 41 , 42 ]. In fact, the occurrence of strains resistant to AMP, AMC, SXT and TET [ 43 , 44 ], and the occurrence of ESBL producers resistant to at least one more class of non β-lactam antibiotics, have been formerly described in Greece [ 45 ].…”
Section: Discussionsupporting
confidence: 83%
“…ESBL-producing E. coli strains presented co-resistances to fluoroquinolones ( n = 49), aminoglycosides ( n = 31), TETs ( n = 26) and SXT ( n = 46), confirming previously reported antimicrobial resistance patterns of ESBL-producing E. coli [ 39 , 40 , 41 , 42 ]. In fact, the occurrence of strains resistant to AMP, AMC, SXT and TET [ 43 , 44 ], and the occurrence of ESBL producers resistant to at least one more class of non β-lactam antibiotics, have been formerly described in Greece [ 45 ].…”
Section: Discussionsupporting
confidence: 83%
“…Molecular studies have consistently shown that ESBL genes in Enterobacteriaceae isolates are physically associated with MGEs that carry other resistance genes mediating resistance to an unrelated class of antibiotics [ 110 , 111 ]. Co-resistance to multiple classes of antibiotics such as fluoroquinolones, tetracyclines, chloramphenicol, aminoglycosides, sulfonamides, and /or trimethoprim has been frequently reported in E. coli and Salmonella species isolated from dairy cattle and other food-producing animals (e.g., in Pigs and poultry) in the USA and elsewhere (e.g., India, China, and Egypt [ 18 , 24 , 111 , 112 , 113 , 114 , 115 ].…”
Section: Molecular Epidemiology Of Extended-spectrum Beta-lactamases ...mentioning
confidence: 99%
“…Therefore, we have a relatively large sample of participants drawn from the general population in Southern Germany, the Netherlands, and Romania. In contrast, other similar studies explored risk factors in large sample sizes from only one country (63), in specific high-risk populations such as farmers (32)(33)(34)(35)37,38,40,42,43) and slaughterhouse workers (31), healthcare workers and patients (39,44,45,47,48), or travelers (8,10,14,18,20,25,26,46), or in convenience samples of students (16,17,21,22). Further, when exploring frequency of travel, we considered all areas of the globe, and did not limit ourselves to low-and-middle income countries or other areas that would have been otherwise considered a priori as high-risk areas for AR.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential risk factors include travels to high-risk areas for AR , nutrition (28,29), health status (21,25), and occupation (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). However, most of the studies examining potential risk factors focus on high-risk populations such as travelers (8,10,14,18,20,25,26,46), healthcare workers and patients (39,44,45,47,48), swimmers (49)(50)(51), farmers (32)(33)(34)(35)37,38,40,42,43), and slaughterhouse workers (31), and often using small convenience samples of e.g. students (16,17,…”
Section: Introductionmentioning
confidence: 99%